Comparison of Prevalence of Synovitis by Ultrasound Assessment in Subjects Exposed or Not to Self-Reported Physical Overexertion: The Monday’s Synovitis - C. A. Guillén Astete; A. Boteanu; A. Zea Mendoza (The Scientific World Journal)
Objective. To compare the proportion of synovitis detected by ultrasonographic study (USS) of the hands, in subjects with no rheumatologic known disease according to self-reported level of overexertion performed the day before. Methods. 407 consecutive volunteers were enrolled in a twelve-month period and underwent an ultrasound assessment of the hand. All studies were performed on Monday or Friday. Subjects were grouped according to their self-reported overexertion carried out the day before. Presence or absence of ultrasonographic findings compatible with synovitis was compared between groups. Results. 95.8% of those tested on Friday had made no overexertion the day before the study, while 30.2% of those assessed on Monday declared to have carried out an overexertion. Presence of carpal synovial hypertrophy, synovial fluid/effusion, and power-Doppler signal was statistically higher in subjects who carried out an overexertion the day before the study than the rest of subjects when the dominant hand was assessed. Globally, presence of any synovitis ultrasonographic finding was statistically higher in subjects who were studied on Monday than Friday (34.9% versus 12.1%) and in subjects who self-reported an overexertion the day before compared to the rest of subjects (47.7 versus 11.5%). Conclusions. In general, we recommend performing the USS as many days as possible after the most recent overexertion.